An examination of value enhancing enterprise risk management implementation framework for Malaysian public listed companies / Lai Fong Woon - Lai , Fong Woon (2011)
Enterprise risk management or ERM is fast ascending the corporate agenda globally. Its relevancy and popularity as a management technique are abetted by the changing business practices and burgeoning regulatory requirements on risk management. ERM is defined as the process of identifying and analyzing risk from an integrated, company-wide perspective in a structured and disciplined approach in aligning strategy, processes, people, technology and knowledge with a purpose of evaluating and managing the uncertainties facing the enterprise as it creates value. ERM essentially lays concern for managing the firm‟s specific risk apart from the systematic risks. However, the neo-classical finance theory (NCFT) postulates that managing firm-specific risk is irrelevant. Nonetheless, this notion is in stark contrast to the phenomenon of increased acceptance of ERM by industry practitioners. As such, this thesis attempts to propose an ERM implementation framework to theorize a model that captures the causal relationships of the risks that are strategically associated with the firms‟ business performance and the cost of capital, e.g. risk premium. This thesis highlights the notion of managing firms‟ unsystematic (specific) risk via an ERM implementation framework that leads to the enhancement of shareholders‟ value. The mechanism through which the firms‟ value enhancement takes place is theorized by a strategic conceptualization of risk premium model. The model cites managing the firm‟s three classes of unsystematic risk, namely tactical risk, strategic risk, and normative risk. The specific aims of this thesis are fourfold: (i) to examine the depth of penetration of ERM practices among the public listed companies in Malaysia; (ii) to examine how an effective implementation process of ERM will bring about value-enhancing outcome to Malaysia public listed companies (PLCs); (iii) to analyze the value proposition hypotheses of corporate risk management as the determinants for ERM practices; and (iv) to investigate the validity of the theorized value creation transmission mechanism of the proposed ERM framework via the strategic conceptualization of risk premium model. The data is collected through questionnaires survey from 128 PLCs on the Malaysian stock exchange. Variables in the questionnaire are measured in 5-point Likert‟s scale. The analyses encompass factor analysis and structural equation modeling (SEM). Outcomes of the factor analysis provide inputs (the measurement model) for the SEM analysis. The SEM validates the theorized causal relationships among the three constructs, i.e. ERM implementation challenge, ERM implementation intensity, and perceived ERM benefit measures. The modified model incorporates a second-order factor model which presents improved overall goodness-of-fit values than the proposed model. Apart from that, the analytic also comprises bivariate correlation analysis of hypotheses testing in relation to the various aspects of: (i) the value maximization theory of ERM practices; and (ii) the value creation transmission mechanism of the proposed ERM implementation framework. The analysis results conclude the following: (i) that all causal relationships (structural model) under SEM examination indicate significant parameters; (ii) that ERM implementation has significant positive associations with value maximization theories of risk management; (iii) that ERM implementation has significant positive v effects in reducing the firm‟s tactical and strategic risks with the consequence of lowering the firm‟s risk premium.